2012
DOI: 10.1111/j.1476-5829.2012.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Feline exocrine pancreatic carcinoma: a retrospective study of 34 cases

Abstract: Thirty-four cases were reviewed in this retrospective study for information on clinical presentation, prognostic indicators, survival time and response to various therapies. The most common presenting clinical signs were weight loss, decreased appetite, vomiting, palpable abdominal mass and diarrhoea. Metastatic disease was confirmed in 11 cats. The overall median survival was 97 days. The median survival times for patients who received chemotherapy or had their masses surgically removed was 165 days. Those pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 33 publications
3
84
0
Order By: Relevance
“…However, DM in cats can also result from other causes. Hypersomatotropism (acromegaly) has been estimated to cause 25% of diabetes cases in cats in the United Kingdom, and other recognized causes include hyperadrenocorticism, pancreatic disease and diabetogenic drug administration …”
mentioning
confidence: 99%
“…However, DM in cats can also result from other causes. Hypersomatotropism (acromegaly) has been estimated to cause 25% of diabetes cases in cats in the United Kingdom, and other recognized causes include hyperadrenocorticism, pancreatic disease and diabetogenic drug administration …”
mentioning
confidence: 99%
“…In this case report, pancreatic carcinoma was identified as the underlying cause of the chyloabdomen. Linderman et al (2013) previously reported 34 feline cases of pancreatic carcinoma; chylous ascites was present in one cat in this series. In human medicine, direct malignant cells invasion into lymphatic vessels and obstruction of lymphatic flow by lymph node metastatic infiltration are thought to explain chyloabdomen formation during neoplastic disease (Al-Busafi et al, 2014).…”
Section: Introductionmentioning
confidence: 50%
“…Management of chyloabdomen first relies on treatment of the underlying cause when possible, as in this case pancreatic carcinoma. Pancreatic carcinoma is an uncommon tumor in cats with a high metastatic rate and a poor prognosis (Linderman et al, 2013). Abdominal effusion is a negative prognostic indicator, with a median survival time of only 30 days (Linderman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that tumors of the exocrine pancreas can predispose cats to DM. 12 It is therefore possible that the pancreatic adenocarcinoma seen in our study caused DM by infiltrating and disrupting viable islets.…”
Section: Discussionmentioning
confidence: 97%